The pattern of suicide poisoning cases in the Tertiary care Centre in Chengalpet district, Tamil Nadu, India - Veerasamy, R. Swaminathan; Raja, V. Pragadeesh; Muthukumar, T.; Kalaivani, A. (International Journal Of Community Medicine And Public Health, 2021)
Background: Suicide is an important public health problem, every year 800000 people due to suicide, Suicide is the third leading cause of death in 15-19-year-old only. Most (79%) of the suicide happened in low and middle-income countries. Among them consuming poisoning is 25.8%. In India 2019 incidence of suicides 10.4 per one lakh (1,00,000) of population. Tamil Nadu is the state of India sharing most of the suicide deaths, second position (9.7%) in 2019 next to Maharashtra (13.6%). Methods: This is a Hospital-based cross-sectional study, this study was conducted among suicide patients who consumed poison by using nonprobability, consecutive sampling. A pretested questionnaire was administered, and information regarding socio-demographic factors, type of poisoning, and outcome of poisoning was obtained. Statistical analysis was done through Statistical package for social sciences (SPSS) version 21. Results: Of 111 suicide poisoning patients admitted, were female (50.5%) and the majority were from a rural area (70.3%). Among suicidal, tablet poisoning was predominant (27.7%), followed by Organophosphorus poisoning (26.8%) and rat killer poisoning (17.1%). The major reason for suicidal poisoning was family problems (58.6%), and the majority of Suicidal poisoning was more among the age group of 11–30 years (67.6%) and middle socioeconomic status (50.5%). The majority of patients were admitted to the hospital with median days of 2 days (range 1-12). Among 111 patients 109 are cured and discharged and death of 2 cases. Conclusions: Suicides are avoidable and preventable deaths, there are so many measures are there in individuals levels particularly high-risk persons and community level also. So many poisoning cases are tablets and organophosphorus so to take steps for reducing access for that like legislative measures and regulations. Early identification of the mentally disturbed persons and to give counselling.